Does regionalism matter? Local politics and foreign direct investment in South Korea. Issue 3 (8th July 2019) - Kim, Dong-Hun; Paek, Sunwoo
Abstract : Purpose: The purpose of this paper is to examine how political/authoritarian regionalism affects foreign direct investment (FDI) in sub-national states in South Korea. Design/methodology/approach: This paper employs statistical analysis to examine the relationship between regionalism and FDI, along with historical description of regionalism in South Korea. Findings: The analyses suggest that not only authoritarian regionalism influence foreign investment to the region but also political regionalism matters. Sub-national states with higher authoritarian regionalism receive less foreign investment while sub-national states with high political regionalism, which imply political stability, receive more FDI than others. Originality/value: The paper examined how local politics influence foreign investments in South Korea, and suggests stronger decentralization will positively influence FDI in the future.